(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Internet shopping is now a sea change that has implications with both consumers and advertisers. Digital transformation will played a great role as in upcoming easy access to financial divisions and business services in a rising economy. To combat deceptive conduct, the rising use of smart mobile operators and the World Wide Web as a niche product for exchange of goods and services and foreign investment needs a stronger attention on t s security. The advances in internet technology has created havoc in almost every element of a lives. E-commerce has a lot of benefits that boost customer — and give conveniences in any place and enabling a company to get a higher market share. As a consequence of extensive internet usage, e-commerce has risen in popularity, and companies, particularly continue, and are rapidly moving to this option as a differentiating strategic framework. This paper discusses about E-commerce, E commerce providers, Benefits, and Challenges. This paper can be used by researchers for further study in E commerce in future.